Paleoecological implications of dental mesowear and hypsodonty in fossil ungulates from Kanapoi. Issue 140 (March 2020) - Dumouchel, Laurence; Bobe, René
Abstract: The Pliocene site of Kanapoi is key to our understanding of the environmental context of the earliest species of Australopithecus. Various approaches have been used to reconstruct the environments of this site, and here we contribute new data and analyses using mesowear and hypsodonty. The dental traits of 98 bovids, suids and rhinocerotids from Kanapoi were analyzed using these proxies. Results indicate that most of the animals analyzed had a relatively abrasive diet. Bovids in the assemblage incorporated more grass into their diet than do modern species of the same tribe or genus. Although Pliocene Kanapoi likely had complex environments, our analysis indicates that grassy habitats were a dominant component of the ecosystem, a conclusion that supports the results of previous investigations of the paleoecology of the site.